BRANDING POSITIONING & VALUE DELIVERY & MARKETING COMMUNICATION ON SUCCESSFUL BUSINESS LONG TERM GROWTH - Rubedo, Hendar; Narimawati, Umi; Syafei, M Yani (Jurnal Soshum Insentif, 2023)
Objectives of the research are to understand the influence of Branding Positioning, Value Delivery and Marketing Communication on Successful Business Long Term Growth. Quantitative approach using survey method is used in studying 30 SME business organizations in Bandung. Structural equation modelling based on covariance is used to analyse data. Results of the study are as follows: 1) Branding Positioning, Value Delivery and Marketing Communication affect significantly on Successful Business Long Term Growth simultaneously; 2) Branding Positioning affects significantly on Successful Business Long Term Growth partially; 3) Value Delivery affects significantly on Successful Business Long Term Growth partially; 4) Marketing Communication affects significantly on Successful Business Long Term Growth partially. Thus, business long term growth is important for the business organizations in order to gain competitive advantage and profit.